AMPLITUDE LOSS OF THE HIGH-FREQUENCY FLICKER ELECTRORETINOGRAM IN EARLY DIABETIC RETINOPATHY. Issue 10 (October 2019) - McAnany, J. Jason; Park, Jason C.; Chau, Felix Y.; Leiderman, Yannek I.; Lim, Jennifer I.; Blair, Norman P.
Abstract : Purpose: To evaluate retinal dysfunction in diabetic patients who have mild or no nonproliferative diabetic retinopathy (DR) using the high-frequency flicker electroretinogram. Methods: Light-adapted flicker electroretinograms were recorded from 15 diabetic patients who have no clinically apparent retinopathy, 15 diabetic patients who have mild nonproliferative DR, and 15 nondiabetic, age-equivalent controls. Electroretinograms were elicited by full-field flicker at 2 temporal frequencies, 31.25 and 62.5 Hz, and were recorded using conventional techniques. Amplitude and timing of the flicker responses were compared among the groups and correlated with clinical characteristics including age, acuity, disease duration, and HbA1c. Results: The 31.25-Hz flicker amplitude was slightly, but nonsignificantly, smaller for subjects with no DR and mild nonproliferative DR, compared with the control group (both t < 1.38, P > 0.31); small, nonsignificant response delays for both patient groups were also observed (both t < 1.57, P > 0.12). By contrast, there were significant amplitude reductions for the 62.5-Hz flicker stimulus: mean amplitude was reduced by 32% for subjects with no DR and by 41% for subjects with mild nonproliferative DR (both t > 2.92 and P < 0.01). Response timing at 62.5 Hz did not differ significantly from control for either group (both t < 1.2 and P > 0.39). Electroretinogram amplitude and timing were not correlated significantly with clinical characteristics. Conclusion: The 62.5-Hz flicker electroretinogram is useful for evaluating retinal dysfunction in diabetic patients who have mild or no DR because this response can be significantly reduced. Attenuation of the high-frequency flicker electroretinogram, which is primarily generated by bipolar cells, suggests a relatively early retinal site of neural dysfunction. Abstract : Retinal dysfunction was evaluated in diabetic patients who have mild or no nonproliferative diabetic retinopathy using the high-frequency flicker electroretinogram. The results show that the 62.5-Hz flicker electroretinogram is a useful, clinically relevant measure of dysfunction, and the pattern of response abnormalities suggests an early retinal site of disease.